Mary Poppins returns [videorecording (DVD)] - Marshall, Rob; Blunt, Emily; Miranda, Lin-Manuel, 1980-; Whishaw, Ben, 1980-; Streep, Meryl; Van Dyke, Dick; Firth, Colin, 1960-; Lansbury, Angela, 1925-; Travers, P. L. (Pamela Lyndon), 1899-1996 (Disney DVD., 2019)
After Mary Poppins departed London, Jane and Michael Banks grew up into loving and responsible adults. When Michael becomes a single father of three children after the death of his wife, Mary Poppins revisits the Cherry Tree Lane home again to try to help Michael and his family cope and move beyond their grief. Time passes quickly for most normal mortals. Mary Poppins has never been normal. Although it's now the 1930s, she looks exactly the same. Her message to Michael, Annabel, John, George and Ellen, the family's housekeeper, about enjoying life and loved ones is also still the same.